Analysis of preoperative and postoperative depression and anxiety in patients with osteochondral lesions of the talus - Cao, ShiHang; Zan, Qiang; Lu, Jun; Li, Yi; Li, BingBing; Zhao, Hang; Wang, Tao; Xu, JunKui (Frontiers in Psychiatry, 2024)
Purpose: This study aims to investigate the psychological status of patients with Hepple V osteochondral lesions of the talus (OLT) and evaluate the effect of autologous osteoperiosteal transplantation (AOPT) on their psychological well-being.Methods: Fifty patients with Hepple V OLT who underwent AOPT at the Comprehensive Foot and Ankle Surgery Ward of Xi'an Honghui Hospital from November 2021 to May 2023 were included in this study. The patients were divided into two groups based on the presence or absence of preoperative symptoms of anxiety/depression. Group A comprised patients with preoperative symptoms, while Group B included patients without such symptoms. Preoperative and final follow-up assessments included the Hospital Anxiety and Depression Scale for evaluating anxiety and depression, the visual analogue scale for pain assessment, and the American Orthopaedic Foot and Ankle Society scores for assessing ankle and hindfoot function.Results: Among the 50 Hepple V OLT patients who obtained complete follow-up, twenty-four had preoperative symptoms of anxiety/depression, with an incidence rate of up to 48%. Patients in Groups A and B showed significant improvement in all evaluation indexes after AOPT compared to the preoperative period, but the overall prognosis of Group A was poorer than that of Group B.AOPT can effectively improve patients' pain, functional activities, and psychological status, and there is a significant correlation between patients' preoperative psychological status and prognosis.